The attitudes of people with disabilities who participated in vocational rehabilitation and specialists towards possibilities for application of vocational training and employment models - Tomėnienė, Laima (Social Welfare: Interdisciplinary Approach, 2016)
The article deals with the attitude of people with disabilities who participated in vocational rehabilitation and vocational training specialists towards the possibilities for application of vocational training models and models of workplaces for the employment of people with disabilities in Lithuania and Ukraine. The results of an on-line questionnaire-based quantitative research are introduced. It was found out that when choosing a model of vocational rehabilitation and model of workplaces for the employment of people with disabilities in each of the countries the historical, cultural, religious aspects must be regarded and country’s development, tradition and environment as well as the completeness of the vocational rehabilitation and employment model must be assessed
Keywords: person with disabilities; model of vocational rehabilitation; vocational training specialist; employment model; vocational rehabilitation